FARMER’S PERCEPTION OF CLIMATE CHANGE AND ITS ASSOCIATION WITH DEMOGRAPHIC CHARACTERISTICS IN MAIZE PRODUCING AREA OF NORTHERN, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2021)
This study was designed to found farmers’ perception on climate change and weather changeability using farmers’ demographic information to analyze gender exertion with education level in maize producing areas of the northern region, and its impacts on crop yields. Purposive sampling was used to select a sample size of 400 households. Information was composed from heads of households using a questionnaire and the data obtained were analyzed using statistical analysis. The results showed that farmers perceived climate change and weather variability correctly. The result of the independent-sample t-test on-farmers’ perception about climate change and farming status shows that there was a significant difference in perception of climate change between farmers and non-farmers. chi-square cross-tabulation also demonstrated that there is a significant association between farmers’ level of perception of climate change and gender. Lastly, the study outcome indicates that there was no significant difference in farmers’ perception based on the educational level of the farmers. These findings will be used by both institutions and government in formulating policies and funding for better maize production and agricultural practice in genera
Keywords: climate change, demographic, farmers, maize production, perception